Relationship between knowledge and patient anxiety on CT scan examination at radiology installation of rsud dr. Gunawan mangunkusumo Semarang regency - Suraningsih, Nanik; Prayoga, Aryadiva Nugrahaning; Alfiani, Novita (Jurnal EduHealth, 2024)
In patients who will perform CT Scan examination when entering the examination feel fear, feel uneasy, restless, and often feel fear because there is an examination table and there is a large circular device. This study aims to describe, know, and analyze the relationship between knowledge and anxiety of CT Scan radiography examination patients in CT Scan radiography examination at Radiology Installation of RSUD dr Gunawan Mangunkusumo Kab Semarang. Descriptive quantitative research type. The population in this study were all patients of CT Scan examination in Radiology Installation of RSUD Dr. Gunawan Mangunkusumo Kab Semarang. The sample was 30 patients of CT Scan examination in Radiology Installation of RSUD dr Gunawan Mangunkusumo Kab Semarang. Data collection with quisione. Data analysis using nonparametric, namely Rank Spearman correlation. The results of the Spearman rank test obtained a Spearman rank correlation value (Rs) of -0.615 with a strong correlation level category and a significance value (p-value) of 0.000. The significance value of the test is smaller than 0.05 (0.000 <0.05) so that the test decision is H_0 rejected which means that there is a significant relationship between patient's knowledge of CT scan radiography examination and patient's anxiety at CT scan examination. Furthermore, the value of the Spearman rank correlation coefficient is negative (-0.615), meaning that the higher the level of patient's knowledge of CT scan radiography examination, the higher the level of patient's anxiety.